Nocturnal Bees Feed on Diurnal Leftovers and Pay the Price of Day – Night Lifestyle Transition - Somanathan, Hema; Krishna, Shivani; Jos, Elsa M.; Gowda, Vishwas; Kelber, Almut; Borges, Renee M. (Frontiers in Ecology and Evolution, 2020)
1. Bees exemplify flights under bright sunlight. A few species across bee families have evolved nocturnality, displaying remarkable adaptations to overcome limitations of their daylight-suited apposition eyes. Phase inversion to nocturnality in a minority of bees that co-exist with diurnal bees provide a unique opportunity to study ecological benefits that mediate total temporal niche shifts. While floral traits and sensory modalities associated with the evolution of classical nocturnal pollination syndromes, e.g. by bats and moths, are well-studied, nocturnality in bees represent a poorly understood, recently invaded, extreme niche. 2. To test the competitive release hypothesis, we examine how nocturnality shapes foraging by comparing pollen loads, nest pollen and flower visitation of sympatric nocturnal and diurnal carpenter bees. We predicted that nocturnal bees primarily use night-blooming flowers, show little/no resource overlap with diurnal species and competitive release favours night-time pollen collection for provisioning. 3. Contrarily, we found substantial resource overlap between nocturnal and diurnal bees. Flower opening times, floral longevity and plant abundance did not define nocturnal flower use. Smaller pollen loads on nocturnal foragers suggests subsistence on resource leftovers largely from diurnal flowers. Greater pollen types/diversity on nocturnal foragers indicates lower floral constancy compared to diurnal congenerics. Reduced activity during new moon compared to full moon suggests constraints to nocturnal foraging. 4. Invasion and sustenance within the nocturnal niche is characterised by: i)opportunistic foraging on residual resources as indicated by smaller pollen loads, extensive utilisation of day-blooming flowers and substantial overlap with diurnal bees, ii)generalisation at two levels – between and within foraging trips as indicated by lower floral constancy, iii)reduced foraging on darker nights, indicating visual constraints despite sensitive optics. This together with smaller populations and univoltine breeding in nocturnal compared to multivoltine diurnal counterparts, suggest that nocturnality imposes substantial fitness costs. 5. In conclusion, the evolution of nocturnality in bees is accompanied by resource generalisation instead of specialisation. Reduced floral constancy suggests differences in foraging strategies of nocturnal and diurnal bees which merits further investigation. The relative roles of competition, floral rewards and predators should be examined to fully understand the evolution and maintenance of nocturnality in bees.